Influence of Traveloka's Instagram Social Media Advertising on Sumba on Followers' Visit Decisions - Gunawan, Afifah Zahra; Kencana, Woro Harkandi (PT. Riset Press International, 2024)
The latest developments in information technology have provided quick and technically straightforward access. In the rapidly evolving world of the internet, various types of e-commerce, such as online travel agent (OTA) companies, have emerged. Tourism in Indonesia is currently considered one of the significant influences in the country. Traveloka is an online travel agent used for booking tickets and various accommodations online. Additionally, Traveloka is known for its active presence in advertising on various social media platforms. The aim of this research is to determine the Influence of Traveloka's Instagram Social Media Advertising on Sumba on Followers' Visit Decisions. This study employs communication theory (S-O-R) or Stimulus-Organism-Response. The research method is quantitative, involving several data analysis techniques to analyze the obtained data from questionnaire distribution, including Normality Test, Correlation Test, and Simple Linear Regression Test to understand the extent of the influence among the variables being studied using SPSS. The research concludes that Instagram advertising influences visitation decisions. The hypothesis can be interpreted as Instagram advertising having an impact on Visit Decisions.